Causes of Delayed Hospitalization In Periampullary Carcinoma and Its Correlation With Perioperative Outcome - Sobhan, Sarwar Ahmed; Khan, Arif Salam; Das, Bidhan Chandra; Chowdhury, Md Mohsen; Khan, Md Zulfiqur Rahman; Sharmin, Farzana (Journal of Dhaka Medical College, 2016)
Abstract not available J Dhaka Medical College, Vol. 24, No.1, April, 2015, Page 17-23